2020
DOI: 10.1101/2020.11.22.20236398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal obesity before pregnancy predicts offspring blood pressure at 18 years of age: A causal mediation analysis

Abstract: ImportanceHypertension is the second most common pediatric chronic disease in Westernized countries. Understanding the natural history of hypertension is key to identifying prevention strategies.ObjectiveExamine the relationship between maternal pre-pregnancy body mass index (BMI) and offspring blood pressure at 18 years and the mediating role of growth throughout childhood and adolescence.Design, Setting, and ParticipantsWe performed multivariable regression and causal mediation analyses within 3217 mother - … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Maternal overweight is a risk factor for foetal macrosomia and it increases the risk of development of obesity throughout childhood and adolescence (114)(115)(116)(117). High maternal weight during all three trimesters of pregnancy increases the risk of elevated birth weight of offspring (118,119).…”
Section: Effects Of Maternal Overnutrition On Body Weight and Fat Con...mentioning
confidence: 99%
See 3 more Smart Citations
“…Maternal overweight is a risk factor for foetal macrosomia and it increases the risk of development of obesity throughout childhood and adolescence (114)(115)(116)(117). High maternal weight during all three trimesters of pregnancy increases the risk of elevated birth weight of offspring (118,119).…”
Section: Effects Of Maternal Overnutrition On Body Weight and Fat Con...mentioning
confidence: 99%
“…The meta-analysis of clinical studies showed that excessive gestational weight gain increased the risk of childhood obesity by 33% (120). The proposed mechanisms underlying these associations include abnormal placental transfer, epigenetic mechanisms, and altered peripheral and central metabolic profile in offspring (114,115).…”
Section: Effects Of Maternal Overnutrition On Body Weight and Fat Con...mentioning
confidence: 99%
See 2 more Smart Citations